The Role of Student Management in Improving Student Discipline in Elementary Schools - Imas Fatmawati (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2026)
The challenge in maintaining student discipline in elementary schools is still a concern, including in SD Negeri 3 Pamotan, some students are less aware of school rules, student management is the right solution to overcome the problem of lack of discipline. The formulation of the problem in this thesis is How is student management implemented in SD Negeri 3 Pamotan to improve student discipline and what are the inhibiting and supporting factors of student management in improving student discipline in SD Negeri 3 Pamotan. This study aims to describe the role of student management in improving student discipline in SD Negeri 3 Pamotan. The main focus of this study is how the implementation of student management in SD Negeri 3 Pamotan and the supporting and inhibiting factors that influence it. This study uses a qualitative method with data collection techniques in the form of observation, interviews and documentation. The results of the study show that student management in SD Negeri 3 Pamotan is implemented through various activities involving behavioral coaching, attendance monitoring and implementation of school rules. The main supporting factors in the implementation of this management include the active involvement of teachers, parental support and a culture of discipline that has been embedded in the school. Inhibiting factors include students' lack of awareness of the importance of discipline, family background, and limited supporting facilities. With focused and consistent student management, student discipline levels have shown significant improvement.